Comparison of nylon‐flocked swab and Dacron swab cytology for anal HSIL detection in transgender women and gay, bisexual, and other men who have sex with men. Issue 4 (26th March 2019) - Wiley, Dorothy J.; Hsu, Hilary K.; Ganser, Martha A.; Brook, Jenny; Elashoff, David A.; Moran, Matthew G.; Young, Stephen A.; Joste, Nancy E.; Mitsuyasu, Ronald; Darragh, Teresa M.; Morris, David H.; Martínez‐Maza, Otoniel M.; et al.
Abstract : Background: An anal histological high‐grade squamous intraepithelial lesion (hHSIL) is an anal cancer precursor. Experts recommend Dacron swab anal cytology as a primary screen for anal hHSILs, especially among human immunodeficiency virus–infected and –uninfected men who have sex with men (MSM). Studies have shown that Dacron cytology inaccurately predicts anal hHSILs and results in unnecessary diagnostic procedures. Nylon‐flocked (NF) swabs have been shown to trap pathogens and cells well. Thus, this study compared test characteristics of anal cytology using NF and Dacron swab collection protocols to predict anal hHSILs. Methods: A single‐visit, randomized clinical trial compared NF and Dacron swab anal cytology specimens to predict high‐resolution anoscopy and biopsy–diagnosed anal hHSILs. Data for 326 gay men, bisexual men, other MSM, and male‐to‐female transgender women contributed descriptive and tabular statistics with which unadjusted and fully adjusted logistic regression models were constructed. The models estimated the odds of hHSILs, test accuracy (area under the curve [AUC]) and sensitivity, and specificity as well as the positive and negative predictive values of abnormal NF and Dacron cytology for predicting hHSILs. Results: In the fully adjusted model, the sensitivities for NF and Dacron cytology were nearly equal (48% vs 47%), but the specificity was higher with NF cytology (76% vs 69%). Comparisons of the areas under receiver operating characteristic curves showed that NF cytology alone predicted hHSILs better than the covariate model (AUC, 0.69 vs 0.63; P  = .02), but NF and Dacron cytology comparisons showed no statistically significant differences (AUC, 0.69 vs 0.67; P  = .3). Conclusions: NF cytology and Dacron cytology provide modest sensitivity, but NF cytology has higher specificity and accuracy, and this is important for lowering the costs of population‐based screening. Abstract : Fully adjusted multivariable models suggest that nylon‐flocked swab cytology and Dacron swab cytology provide modest sensitivity, but nylon‐flocked cytology shows higher specificity and overall accuracy for predicting histological high‐grade squamous intraepithelial lesions, which are cancer precursors. Improved test performance in high‐risk populations such as gay, bisexual, and other men who have sex with men and transgender women will improve mass screening at lower health care costs.